The establishment of environmental court in Indonesia - Achmad Romsan; Suzanna Mohamed Isa (Penerbit Universiti Kebangsaan Malaysia, 2016)
Environmental degradation has caused numerous disasters in many parts of the world. Indonesia, too, has had her share of such catastrophes. The liquid waste in Ciujung River, forest fires and haze of North Sumatera, pollution of Way Seputih River and volcanic mudflow in Sidoarjo are a few examples. As such, the establishment of the Special Environmental Court under the legal system in Indonesia is urgent. In the District Court, victims of environmental polution and degradation are people who are in a weaker position when faced with big industrial companies. The verdicts of the courts do not reflect environmental justice. Although the Indonesian Environmental Management Acts (EMA) has undergone three amendments, it still lacks the necessary bite. This article seeks to provide input for the Indonesian Government concerning the urgent need for the establishment a special environmental court under the General Court System.